Development of Plantar-Pressure Estimation Method Based on Continuous Plantar Images - Iijima, Yuka; Yamakoshi, Takeshi; Mizoguchi, Hiroshi; Takemura, Hiroshi (British Journal of Healthcare and Medical Research, 2016)
We propose a novel plantar-pressure estimation method using high-resolution plantar images. The proposed method can calculate the plantar-pressure distribution, ground reaction force, and center-of-pressure (COP) trajectory based on the weight of a subject, contact-area size, and brightness distribution of a plantar image captured by a high-speed camera. Four experiments are conducted to evaluate the proposed method. First, the relationship between the contact area/pressure condition and brightness distribution of the image is investigated. The result shows that the brightness increases according to the area size under the same pressure condition. Second, the plantar-pressure distribution calculated by the proposed method is compared with that of commercial pressure sensors. The results demonstrate that the plantar-pressure characteristics of the subject even in a small region are unambiguously represented. Third, the ground reaction force estimated by the proposed method is compared with that of the commercial force plate. The root mean square error (RMSE) is 16% of the maximum ground reaction force. The COP trajectory calculated by the proposed method is compared with the result obtained using the force plate. The averages of COP.x and COP.y RMSEs are calculated as 6.0 and 28.6 mm, respectively, which suggest that the proposed method can calculate the pressure distribution, ground reaction force, and COP trajectory. We apply the proposed method to a developed caterpillar-type transparent treadmill and demonstrate that the proposed method can be used for continuous plantar-pressure distribution measurement.